The Uncertain Legacy of Crisis : European Foreign Policy Faces the Future - Youngs, Richard, 1968- (Book collections on Project MUSE., 2013)
The European Union is mired in the worst crisis it has seen for many decades. And the crisis does not stop at Europe's edge. It threatens to undercut the EU's ambitions to develop a coherent and active foreign policy, but it is also forcing European states to reevaluate their approach to security and defense. Richard Youngs examines the legacy of the crisis and what it will mean for the EU's international role. The fallout undermines the EU's foreign policy capacity and tarnishes its normative brand, compelling some member states to focus on realpolitik and their own national-level po.